A comparative study of antenatal health care at Anganwadis in five rural areas at Rushikonda, Visakhapatnam - Chandrasekhar, Vijayalakshmi (International Journal Of Community Medicine And Public Health, 2023)
Background: Maternal morbidity and mortality are directly linked to the quality of the antenatal care provided at the grassroot level in rural India. Methods: A total of 76 pregnant women attending 5 Anganwadi centres at Yendada 1 and 2, Gollalapalem, Vadapalem and Rushikonda were followed up through their confinement. The data collected were with respect to their height, weight, blood pressure, number of visits, antenatal complications and treatment, post-natal course including breast feeding and difficulties faced by clients during the course of their pregnancy. Results: The five Anganwadi centres were observed to be doing a commendable job in promptly registering pregnant women and ensuring proper antenatal care looking after their nutritional supplements and immunization throughout the course of their client’s pregnancies. There was not a single complication from among the study population due to timely referrals to higher centres. Conclusions: The Anganwadi workers have a good insight into the health problems in their community and were able to communicate effectively in the local dialect. They are doing a commendable job in promptly registering pregnant women, and ensuring that they regularly attend for antenatal visits. They are the backbone of the community and are responsible for positive pregnancy outcomes.